1990
DOI: 10.1172/jci114929
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor-alpha inhibits expression of pulmonary surfactant protein.

Abstract: Tumor necrosis factor-a (TNFa) decreased the expression of pulmonary surfactant proteins SP-A and SP-B in human pulmonary adenocarcinoma cell lines. The effect of TNFa on SP-A content and mRNA in the pulmonary adenocarcinoma cell line, H441-4, was concentration and time dependent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
59
1
2

Year Published

1994
1994
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(69 citation statements)
references
References 45 publications
(30 reference statements)
6
59
1
2
Order By: Relevance
“…Thus, we demonstrated that increased expression of MnSOD in the heart did not cause elevation of other primary antioxidant enzymes as a result of adaptive responses. Our results were in agreement with those reported for transgenic mice overexpressing human MnSOD in the lung in which there were no significant changes in CuZnSOD, GPX, and CAT activities (42). It has been suggested that excessive amount of SOD may increase oxidative damage, and thus, the combination of SOD and CAT or GPX may be necessary to reduce oxidative stress rather than SOD alone (43)(44)(45).…”
Section: Discussionsupporting
confidence: 91%
“…Thus, we demonstrated that increased expression of MnSOD in the heart did not cause elevation of other primary antioxidant enzymes as a result of adaptive responses. Our results were in agreement with those reported for transgenic mice overexpressing human MnSOD in the lung in which there were no significant changes in CuZnSOD, GPX, and CAT activities (42). It has been suggested that excessive amount of SOD may increase oxidative damage, and thus, the combination of SOD and CAT or GPX may be necessary to reduce oxidative stress rather than SOD alone (43)(44)(45).…”
Section: Discussionsupporting
confidence: 91%
“…SP-C gene expression is inhibited after infection and exposure to tumor necrosis factor ␣ and is decreased in lungs of infants with respiratory distress syndrome, pneumonia, and pulmonary edema (27,28). Although SP-C is not required for normal pulmonary mechanics at normal lung volumes, decreased surfactant proteins or phospholipids caused by injury or infection may cause surfactant dysfunction, leading to alveolar instability or acute alveolar collapse as seen in RDS, adult respiratory distress syndrome, or pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…Intraamniotic and simultaneous intraperitoneal injection of EGF increases SP-A concentration as well as the lecithin/sphingomyelin ratio in the amniotic fluid of fetal rhesus monkeys (43). IFN-␥ increases SP-A expression in human fetal lung explants (44) and in adenocarcinoma cells (45). On the other hand, cytokines such as TNF-␣ and -␤ downregulate the synthesis and expression of surfactant proteins and lipids.…”
Section: Discussionmentioning
confidence: 99%